THE EFFECT OF GREEN SHELL POWDER WASTE AS A SUBSTITUTE FOR FINE AGGREGATE IN ASPHALT CONCRETE WEARING COURSE MIXTURE - DANIEL SIMATUPANG; SAHAT MARTUA SIHOMBING; ACHMAD PAHRUL RODJI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Waste, the residue of production that has lost its primary purpose, including garbage and wastewater, is a global problem due to its potential for contamination and the spread of disease. In Indonesia, it is estimated that around 21.88 million tons of waste will be produced in 2021. To address this problem, it is important to find ways to reduce waste, such as using it in asphalt production. In an effort to create a more durable road pavement, researchers have experimented with mussel waste as an additive to improve asphalt quality. This study examined the use of mussel waste to replace fine aggregate in asphalt concrete layers, in the hope of extending the life of the road. When mussel waste powder was substituted for 25% filler in the Asphalt Concrete-Wearing Concrete mixture, Marshall characteristic analysis resulted in a stability value of 2487 kg, VMA 36.51%, flow 3.35 mm, VIM 26.19%, and MQ 742 kg/mm, all of which met the requirements. However, the VFB value of 28.27% does not meet the requirements of Bina Marga 2018. The combination produces a stability value of 2568 kg, VMA 37.31%, flow 3.4 mm, VIM 27.12%, and MQ 756 kg/mm ​​in the variation of green mussel powder waste 50%, all of which meet the requirements. However, the VFB value of 27.31% does not meet the requirements of Bina Marga 2018. The mixture design with the results of the cement filler presentation shows the following composition: 17% for hot bin I, 45% for hot bin II, 32% for hot bin III, 6% for cement filler, and 6% for asphalt.